ANALISIS RASIO EFEKTIVITAS PAD, DAN RASIO EFISIENSI PAD PADA LAPORAN REALISASI ANGGARAN PENDAPATAN DAN BELANJA DAERAH (APBD) UNTUK MENGUKUR KINERJA KEUANGAN KABUPATEN KENDAL - Luceria Putri Natalia Pardede (CV. KAMPUS AKADEMIK PUBLISING, 2024)
This research aims to determine the financial performance of Kendal Regency by analyzing the effectiveness ratio and efficiency ratio of Original Regional Income (PAD) in the Kendal Regency APBD Realization Report. The data used is the Budget Realization Report for the 2018 – 2022 fiscal year. Data analysis uses descriptive statistical methods. The results of the research show that the PAD effectiveness ratio for Kendal Regency for the 2018 - 2022 budget year has an average achievement level of 98.2% of the determined budget, which is considered quite effective. Kendal Regency's financial performance for the 2018 - 2022 budget year based on the PAD efficiency ratio is classified as very efficient with an annual average of 93.2% of the budget determined to be classified as less efficient.